Implementación de las Estrategias de Mercadeo en Salud en Colombia (2023)
Marketing strategies progress has allowed business models to thrive in a sustainable and comprehensive way. Healthcare areas have also been involved with a different, diverse and view of marketing, in line with technology advances and its own social agenda. However, the various implemented marketing strategies have been poorly documented and comprehended, especially in Colombia. That’s why the need to understand the current dynamic that healthcare uses in marketing will allow to determine the possible benefits and current implementation issues. Method: Qualitative-descriptive-state of the art study. Research will be done in databases such as Redalyc, PubMed, Google Academic. Results: Strategies most used in healthcare include social marketing, digital marketing and holistic marketing. Most benefits show a stronger relationship with customers and upgrades of clinical and administrative processes. The greater implementation issues related to moral conflicts of healthcare members regarding marketing practices